Task analysis and application services for client relationship management in national level information sharing for social care - Aki Miettinen; Juha Mykkänen; Marko Suhonen (Finnish Social and Health Informatics Association, 2015)
Use of confidential client information in health and social services requires client relationship by legislation. Approaches for verifying this relationship between care provider and client vary between different countries: in some cases, access logs are analyzed and in other cases, access to information is determined based on the existence and proof of client relationship. We present an approach of client relationship management from national project for social services IT in Finland. The approach is based on analysis of client relationship and case management tasks of users and information systems, and use of application services and system roles which support dynamic access management with client relationship as one of key constituents for access to information. The traditional user rights and access management is not the key area of this article.